Zunehmende Fachkräfteengpässe – Warum sind ländliche Räume besonders betroffen? - Tanja Buch; Michaela Fuchs; Janina Helm; Annekatrin Niebuhr; Jan Cornelius Peters; Georg Sieglen (Wirtschaftsdienst, 2024)
Unternehmen fällt es zunehmend schwer, Stellen zu besetzen. Dabei sind ländliche Räume aktuell offenbar stärker von Fachkräfteengpässen betroffen als städtische Räume. Umfassend analysiert wurden diese regionalen Disparitäten bislang jedoch nicht. Wir untersuchen das Ausmaß von Stadt-Land-Unterschieden, betrachten ihre Entwicklung im Zeitverlauf und zeigen, mit welchen strukturellen Merkmalen die regionale Engpasssituation in Zusammenhang steht. – – Over the past decade, firms' recruitment problems have increased significantly in Germany. We show that skill shortages have been more pronounced in rural areas and that the gap between rural and urban regions has slightly increased. The intensity of a local skill shortage is linked to regional labour market conditions, the occupational composition and the share of small establishments. However, the most important factor is a more advanced demographic change in rural areas. Of all factors considered, the proportion of older workers correlates most strongly with the regional vacancy rate.
Keywords: J11; J22; R23; 330; Arbeitsnachfrage; Fachkräfte; Stadt-Land-Beziehungen; Deutschland; Arbeitsnachfrage; Fachkräfte; Stadt-Land-Beziehungen; Deutschland